The direction of evolution: The rise of cooperative organization - Stewart, John E. (Biosystems, 2014)
Two great trends are evident in the evolution of life on Earth: toward s increasing diversification and towards increasing integration. Diver sification has spread living processes across the planet, progressivel y increasing the range of environments and free energy sources exploit ed by life. Integration has proceeded through a stepwise process in wh ich living entities at one level are integrated into cooperative group s that become larger-scale entities at the next level, and so on, prod ucing cooperative organizations of increasing scale (for example, coop erative groups of simple cells gave rise to the more complex eukaryote cells, groups of these gave rise to multi-cellular organisms, and coo perative groups of these organisms produced animal societies). The tre nd towards increasing integration has continued during human evolution with the progressive increase in the scale of human groups and societ ies. The trends towards increasing diversification and integration are both driven by selection. An understanding of the trajectory and caus al drivers of the trends suggests that they are likely to culminate in the emergence of a global entity. This entity would emerge from the i ntegration of the living processes, matter, energy and technology of t he planet into a global cooperative organization. Such an integration of the results of previous diversifications would enable the global en tity to exploit the widest possible range of resources across the vari ed circumstances of the planet. This paper demonstrates that it's case for directionality meets the tests and criticisms that have proven fa tal to previous claims for directionality in evolution.
Keywords: Direction of evolution; Evolution of a global entity; Evolution of cooperation; Evolutionary progress; Major evolutionary transitions